Solar Dryer with Integrated Energy Unit - Korobka S.; Syrotyuk S.; Zhuravel D.; Boltianskyi B.; Boltianska L. (Problems of the Regional Energetics)
The work is devoted to the issue of the rational use of the solar energy in the technological process of fruit drying based on the use of solar drying devices, which are applied in various sections of the agro-industrial centers of Ukraine. The aim of this research was intensification of the fruits drying process using the solar energy by combining an air collector and drying chamber into a single power unit. To achieve the aim the heat exchange diagnostic techniques with alternative potentials of diffusion and moisture transfer was developed. This technique differs from those existing for the heat exchange research in that it allows the intensity of the moisture evaporation from a unit of the material surface to be calculated, based on the synthesis of the moisture content and the irreversible major laws of processes of the heat exchange characteristics of the fruits drying using the solar dryer. The above model makes it possible to diagnose the heat exchange processes and analyze the mathematical model of the heat exchange processes. It also allows modeling the changeable diffusion and moisture transfer potentials based on the dependences obtained and for the purpose of a further application in the methods and devices development to control the strain-deformed state of the fruits during the drying process. The method is offered for the calculation of diffusion and moisture transfer during drying fruits in the solar dryer.